Image Forensics Tool with Steganography Detection - Joel Melanie, Ed Keneth; Var Naseri, Maryam; Binti Sabri, Nor Afifah (International Journal of Psychosocial Rehabilitation, 2019)
The problem context that inspired and motivated this project idea is that as the quote says a picture or image speaks a thousand words. An Image is forensically rich media it contains a lot of metadata you can extract for any Digital Forensics investigation and it can answer the 3 w’s. which is what (what device is used to capture the picture or Image), where (The location where the picture or image was capture) and when (the exact time and date when the image was capture). The current issues are that most of the current image forensics tools is their output is too complex to understand, for students starting out their studies into digital forensics its quite difficult for them to comprehend some details of their output. The tool will also detect if the image has been tempered with if any hidden messages or items is stored inside using steganography. The project is an Image Forensics Tool with Steganography Detection, which can aid in a digital forensics’ investigation where by the investigator is required to get metadata out of any Digital image.